ҚАДИМГИ ФАРҒОНАНИНГ МАДАНИЯТЛАРИНИ ДАВРЛАШТИРИШ БОРАСИДА АЙРИМ ФИКР-МУЛОҲАЗАЛАР (Scientific journal of the Fergana State University, 2023)
In this article, as a result of research by researchers on the periodization of ancient cultures of Fergana, the materials and their conclusions were analyzed. Experts compared the charts and tables regarding periodization.